Cryptogamic epiphytes as indicators of successional changes in megadiverse lowland rain forests of western Amazonia. (October 2021) - Déleg, Jorge; Gradstein, S. Robbert; Aragón, Gregorio; Giordani, Paolo; Benítez, Ángel
Highlights: Epiphytic cryptogams were significantly affected by succession in Amazonian forests. Tree species richness is a key driver for cryptogamic epiphytes in Amazonian rain forests. The late successional forests are essential for conservation of epiphytic cryptogams. Abstract: The Amazonian rain forests of Yasuni National Park, Ecuador (YNP), count among the world's forests regions with highest biodiversity, but are strongly threatened by deforestation. Cryptogams (bryophytes and lichens) are common and characteristic organisms in these forests, are sensitive to environmental changes, and are considered effective ecological indicators. The objective of this study was to explore the response of epiphytic cryptogams to forest succession in the Amazonian forests of YNP. We hypothesized that alteration of structural and micro-environmental characteristics of the forest, including reduction of canopy cover and lowering of tree species richness, lead to a reduction of species richness and changes in species composition of epiphytic cryptogams. We assessed species richness and composition of cryptogams on the bases of 442 trees in three stage of forest succession (early, intermediate, late), using generalized linear mixed models, multivariate analysis, beta diversity components and Mantel test. We registered 146 species of cryptogams, including 50 of lichens and 96 of bryophytes (39 mosses, 57 liverworts). Diversity of epiphytic cryptogams was highest in late succession forest, and lowest in early succession forest. Major changes in species richness and composition correlated with changes in canopy openness relative to the shift from early to late stages of forest succession. The results demonstrate for the first time the importance of tree species richness for cryptogamic epiphyte richness in Amazonian rain forests. Maintenance of high tree species diversity and structural heterogeneity in late succession forests can considerably contribute to the conservation of the cryptogamic epiphytes of Amazonian rain forests.